The Impact of Work-family Conflict and Emotional Intelligence on Nurse’s Performance at Dr. Pirngadi Hospital - Romauli E. G Siallagan; Arlina Nurbaity Lubis; Sri Eka Wahyuni (Universitas Muhammadiyah Yogyakarta, 2020)
A hospital is one of the healthcare facilities for society. The success of a hospital is indicated by the quality service of the Nurse. A good performance of the nurse is expected to give the best treatment for the patients. A profession as a nurse is not easy for a married woman with children because she has a double function, as a housewife and a nurse. Both functions may impact on the performance of nursing. The study was to identify the impact of work-family conflict (WFC) and emotional intelligence (EI) on the performance of nurses at Dr. Pirngadi Hospital Medan. Quantitative correlation descriptive with a cross-sectional design was applied in this study. The population of the research is 115 nurses. Data were analyzed by using the Spearmen correlation coefficient test. The results show that both WFC and EI impact on the performance of nurses at Dr. Pirngadi Hospital Medan. Mostly nurses (69.6 %) were highly impacted by WFC and 67.8 % of them were in the low level of Emotional Intelligence.